2009
DOI: 10.1136/bmj.b4080
|View full text |Cite
|
Sign up to set email alerts
|

Immobilisation versus immediate mobilisation after intrauterine insemination: randomised controlled trial

Abstract: Objective To evaluate the effectiveness of 15 minutes of immobilisation versus immediate mobilisation after intrauterine insemination. Design Randomised controlled trial. Setting One academic teaching hospital and six nonacademic teaching hospitals. Participants Women having intrauterine insemination for unexplained, cervical factor, or male subfertility. Interventions 15 minutes of immobilisation or immediate mobilisation after insemination. Main outcome measure Ongoing pregnancy per couple. Results 391 coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 5 publications
0
24
0
Order By: Relevance
“…However, the main drawbacks of this technique are possible time wasted while waiting for the bladder to fill and patients' stress due to urgent urination need or early mobilization to urinate after IUI procedure. In addition, the evidence that immobilization for 15 min after IUI increase the pregnancy rate might be argued 6 . However, sharing the knowledge that pregnancy rates were improved with passive uterine straightening, and by emptying the bladder with a Foley catheter after IUI, may encourage patients who have difficulty tolerating the technique.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the main drawbacks of this technique are possible time wasted while waiting for the bladder to fill and patients' stress due to urgent urination need or early mobilization to urinate after IUI procedure. In addition, the evidence that immobilization for 15 min after IUI increase the pregnancy rate might be argued 6 . However, sharing the knowledge that pregnancy rates were improved with passive uterine straightening, and by emptying the bladder with a Foley catheter after IUI, may encourage patients who have difficulty tolerating the technique.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the evidence that immobilization for 15 min after IUI increase the pregnancy rate might be argued. 6 However, sharing the knowledge that pregnancy rates were improved with passive uterine straightening, and by emptying the bladder with a Foley catheter after IUI, may encourage patients who have difficulty tolerating the technique.…”
Section: Discussionmentioning
confidence: 99%
“…Several randomized studies suggest that pregnancy rates may be increased if the woman remains lying down on the examination table for 10-15 min [ 27 ]. A prospective, randomized trial of women treated with clomiphene and IUI found that subjects who remained supine for 10 min after insemination had higher per cycle pregnancy rates (4.4 % vs. 13.3 %) and three-cycle cumulative pregnancy rates (10 % vs. 29 %) [ 28 ].…”
Section: Methodsmentioning
confidence: 97%
“…Saleh et al (2000) reported that if a woman remained in a supine position for 10 min after IUI, the pregnancy rates increased significantly compared with immediate mobilization (13% vs. 4% per cycle). A more recent, larger study by Custers et al (2009) showed that immobilization for 15 min after IUI significantly increased ongoing pregnancy and live birth rates compared to immediate mobilization (OPRs 27% vs. 18%, RR: 1.5, 95% CI, 1.1-2.2; live birth rates 27% vs. 17%, RR: 1.6, 95% CI, 1.1-2.4).…”
Section: Single Versus Double Inseminationmentioning
confidence: 92%